Pengaruh Intellectual Capital terhadap Produktivitas Kerja Pegawai - Mochamad Firmanudin; Sudradjat; Vina Citra Mulyandani (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research was conducted to analyze and prove the effect of intellectual capital on employee work productivity. This research was conducted at the local government of West Bandung Regency. This type of research is a quantitative study, using primary data by distributing questionnaires to financial employees. Respondents in this study were 96 respondents from 27 work units in the local government of West Bandung Regency. The sampling technique used was purposive sampling method in which the respondents who filled out the questionnaire had certain criteria, then the respondents in this study were kept secret so that the respondents could really fill in. The data analysis technique used is simple linear regression and statistical analysis was carried out using the IBM SPSS version 25.0 application. The results of this study indicate that intellectual capital has a positive and significant effect on employee work productivity by 53.5%.